Efektivitas Media Jenga Balok Terhadap Penguasaan Kosakata Bahasa Jawa Ragam Krama Alus di Sekolah Dasar - Kinasih, Nandan Cahya; Mukhlis, Abdul; Prabowo, Dimas Setiaji (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
This research was conducted based on a problem that the researcher found regarding grade IV students at SD Negeri 02 Kajen Pekalongan Regency who did not understand Javanese manners because it was considered difficult to practice. The purpose of this study was to compare the level of Javanese language proficiency of fourth grade students at SD Negeri 02 Kajen before and after using block jenga media. Furthermore, to assess the success of block jenga media on Javanese alus krama skills in Class IV SD Negeri 02 Kajen. This study used a quantitative methodology and a Pre-Experimental Design study conducted at SD Negeri 02 Kajen Pekalongan. The One-Group Pretest-Posttest study was conducted without using a comparison (control) group. There is only one sample class, namely Class IV which has 24 students, so this sample was chosen. In this study, testing methods and documentation techniques were used for data collection. The findings of this study revealed that by using the T-Test according to the one sample T-Test, the pre-test average score was 42.5 while the post-test average score was 77.91. This means that the average difference between before and after the application of block jenga media is significantly different. The N-Gain test produces a value of 0.6238 for the N-Gain score, the mean, or the average value. The effectiveness value of beam jenga media is moderate because the deviation is less than 0.7. The mean or percent average N-Gain value at that time was 62.3810, or 62.3%. If the conspicuousness is between 55% and 75%, it can be said that the use of beam jenga media is quite effective.